Trigonometry (11th Edition) Clone

Published by Pearson
ISBN 10: 978-0-13-421743-7
ISBN 13: 978-0-13421-743-7

Appendix C - Functions - Page 437: 42



Work Step by Step

We are given that $g(x)=-x^{2}+4x+1$. We can plug the given value into the equation and evaluate. $g(-\frac{1}{4})=-(-\frac{1}{4})^{2}+4(-\frac{1}{4})+1=-(\frac{1}{16})+(-1)+1=-\frac{1}{16}-1+1=-\frac{1}{16}+0=-\frac{1}{16}$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.